Closed-loop digital twin system for air cargo load planning operations. Issue 7 (3rd August 2021) - Wong, Eugene Y. C.; Mo, Daniel Y.; So, Stuart
ABSTRACT: Air cargo loading in terminals demands precise planning to ensure efficient operations and minimise costs with limited time in the airport. Real-time visualisation and loading optimisation are becoming increasingly important due to dynamic loading considerations, including the segregation of dangerous goods and inherent lithium batteries, weight balancing, and oversize cargo handling. A closed-loop dynamic air cargo loading digital twin system, integrating a cargo load plan optimisation simulation, multi-dimensional immersive virtual reality system, Internet of Things, and real-time sensors, is proposed for connecting, monitoring and controlling the operations in physical operations and virtual space. A Cave Automatic Virtual Environment (CAVE)-based virtual reality system is used to visualise and experiment with loading procedures. The system uses a feedback loop during sensor data capture to facilitates the decision-making processes on the optimal cargo load plan. Scenarios are discussed demonstrating the impact of the digital twin system on the daily operations of an air cargo terminal, especially the allocation of dangerous goods and special cargo. Load planners can master complex air cargo load planning through the system with optimal solutions generated. The operations of cargo assembly and security screening with digital twins could be further developed for future development.